2020
DOI: 10.3390/app10155301
|View full text |Cite
|
Sign up to set email alerts
|

Mesial Rotation of the Upper First Molar: Association with Anterior Dental Crowding in Mixed and Permanent Dentition

Abstract: The position of the upper first molar (UFM) is currently considered the “key of occlusion”. The purpose of this study was to evaluate the prevalence of the mesiorotated UFM, and its relationship with anterior dental crowding in mixed and permanent dentition. Intra-oral scans of upper dental arches of 180 subjects with mixed dentition and 169 subjects with permanent dentition were retrospectively analyzed to investigate the presence of UFM mesiopalatal rotation and presence of anterior crowding. The occlusal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…To test the accuracy of ClinCheck planning, measurements taken at T2 were analysed in comparison with outcomes planned for the end of the first phase of aligners (T2CC) with a predictability of 82%. These results agreed with those obtained by other studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], reporting that the ClinCheck prospected a greater distal rotation than realized and which is necessary to provide a further correction of mesial rotation movement during the refinement additional phase.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To test the accuracy of ClinCheck planning, measurements taken at T2 were analysed in comparison with outcomes planned for the end of the first phase of aligners (T2CC) with a predictability of 82%. These results agreed with those obtained by other studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], reporting that the ClinCheck prospected a greater distal rotation than realized and which is necessary to provide a further correction of mesial rotation movement during the refinement additional phase.…”
Section: Discussionsupporting
confidence: 92%
“…Plenty of investigations [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] stated a high percentage of mesial-rotation of upper first molars in Class II malocclusion. In 2019, de Oliveira-Viganò et al stated that dental Class II show the highest levels of mesio-palatal rotation of the upper first molars [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are plenty of investigations focused on this topic [5][6][7][8][9]. The prevalence of the mesial rotation in subjects with the presence of Class II malocclusion is about 86%.…”
Section: Introductionmentioning
confidence: 99%
“…Lima et al [6] found a correlation between the severity of Class II division 1 malocclusion and the amount of maxillary first molars' mesiopalatal rotation. Furthermore, Quinzi et al reported that there is an association between upper first molar mesial rotation and anterior dental crowding in permanent dentition, while subjects in mixed dentition with mesial rotation should be considered at a higher risk of dental crowding [7]. In 2011, Giuntini et al [8] investigated the upper first molar mesial rotation in Class II division 1 malocclusion subjects in mixed dentition.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils, T-killer cells, T-active cells, T-suppressor cells, and T-CD8 þ CD38 þ cells emerge as crucial actors in the immune response to COVID-19 and COVIDlike individuals. The intricate dance of immune cells, especially T-lymphocytes and B-lymphocytes, takes center stage in predicting the severity of COVID-19 and the potential efficacy of therapeutic interventions [63][64][65][66][67][68][69][70][71][72][73]. The systemic implications of COVID-19 are illuminated, particularly affecting the lungs, kidneys, and heart.…”
Section: Exploring the Interconnected Landscape Of Interleukins Perio...mentioning
confidence: 99%